IMF Staff papers : Volume 21 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1974)
In this paper, various policy instruments at the disposal of national governments for dealing with the problem of disruptive international capital flows or, more generally, the problem of temporary and reversible payments imbalances, are passed in review. The instruments examined include: separate (dual) exchange markets for capital and current transactions; taxes and subsidies affecting capital transactions or income from capital; official intervention in forward exchange markets; monetary or interest rate policies (including the fiscal-monetary mix); official financing or use of reserves; and floating unitary exchange rates and wider margins. Attention is focused on the device of dual exchange markets, which is evaluated in comparison with each of the other approaches from the standpoint of allocative effects, scope, enforceability, flexibility, and so on. Dual markets, if conducted on appropriate lines, are found to compare favourably overall with most of the other policies, except for floating unitary rates. The paper closes with a suggestion for a system of dual exchange markets with floating rates (subject to appropriate official intervention) on both markets.